Experimental Investigation on the Effect of Graphene Addition on Mechanical Properties of Al8011-T6 Based Fiber Metal Laminate - M. Zakaulla (Archives of Metallurgy and Materials)
Abstract: In the present study, the tensile and flexural properties of lightweight fiber metal laminates composed of Al8011-T6 and carbon fiber/epoxy resin filled with varying weight percentages of graphene (0.0, 0.3, 0.6, 0.9, and 1.2 wt%) were examined under quasi-static loadings for automobile applications. Fibre-metal laminates having different stacking sequences of the same layer thickness are manufactured using the hand layup process. Surface treatment was performed on Al8011-T6 sheet in order to get good adhesion between aluminium and epoxy. With the optimum content of 0.6 and 0.9 wt% of graphene, the tensile and flexural strengths were improved by 15% and 25%, respectively, compared to aluminium fiber metal laminates without graphene for 0/0 fiber layup orientation.